Cell proliferation in the Drosophila adult brain revealed by clonal analysis and bromodeoxyuridine labelling. - von Trotha, J.W.; Egger, B.; Brand, A.H. (Neural Development, 2009)
The production of new neurons during adulthood and their subsequent integration into a mature central nervous system have been shown to occur in all vertebrate species examined to date. However, the situation in insects is less clear and, in particular, it has been reported that there is no proliferation in the Drosophila adult brain.We report here, using clonal analysis and 5'-bromo-2'-deoxyuridine (BrdU) labelling, that cell proliferation does occur in the Drosophila adult brain. The majority of clones cluster on the ventrolateral side of the antennal lobes, as do the BrdU-positive cells. Of the BrdU-labelled cells, 86% express the glial gene reversed polarity (repo), and 14% are repo negative.We have observed cell proliferation in the Drosophila adult brain. The dividing cells may be adult stem cells, generating glial and/or non-glial cell types.